Tribological Behaviour of Nickel Film Deposited on Nickel Substrate - Gokula Deepan1, P.; Kumar2, N.; Rajagopalan2, S.; Dash2, S.; Tyagi2, A.K. (Asian Journal of Chemistry, 2013)
Thin hard and soft coatings are used extensively by industry to combat friction and wear in a wide range of machine tools and moving mechanical assemblies. The strength and all the mechanical properties of the base and functional aspects of the coating can improvise and enhance the performance and life of the components. In this work, thin nickel films were deposited on nickel substrate by electron beam- physical vapour deposition (EB-PVD) technique at different deposition temperature. The deposited film thickness and grain size was found to be varied with deposition temperature. It was observed that the deposition temperature does not affect the surface roughness of the film. The grain size was also higher at higher deposition temperature. The tribological test was conducted using Si3N4 and steel ball at different sliding velocities. The coefficient of friction was found to be lower at the deposition temperature of 300 ºC. The wear dimension also decreases with decreasing the value of the coefficient of friction.